A CODICOLOGICAL AND TEXTOLOGICAL STUDY OF THE QUR’AN MANUSCRIPT MTJ/LT/87 FROM THE NAHDLATUT TUROTS COLLECTION - Muhammad Luqman Hakim Al Qindi (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2026)
Indonesia is one of the countries with the richest manuscript collections in the world, including Islamic manuscripts such as Qur’anic manuscripts. These manuscripts hold significant historical and intellectual value, making their academic study increasingly important. This study analyzes the codicological and textological aspects of the MTJ/LT/87 Qur’anic manuscript from the Nahdlatut Turots Bangkalan collection, while contributing to the academic documentation of Nusantara Qur’anic manuscripts, particularly those from the Madura region. This qualitative study employs a descriptive-analytical approach, using the MTJ/LT/87 Qur’anic manuscript as the primary source and journals, books, and interview results as secondary sources. The findings of this study cover the codicological and textological aspects of the MTJ/LT/87 Qur’an manuscript. Codicological findings include the method of acquisition, storage location, paper type, number of pages, and the language and ink colors used. Textological findings encompass copying errors, scholia, punctuation, waqf marks, and symbols found in the manuscript. This study also produced several significant findings supported by strong arguments. First, copying errors that affect both reading and interpretation. Second, indications that the manuscript follows the al-sajāwandi waqf system. Third, indications that the manuscript originates from Madura despite the absence of provenance data. Furthermore, this study supports Annabel Teh Gallop’s findings on Qur’anic art in Java, including Madura, as evidenced by the use of minimally decorated daluang paper and verse-ending markers in the form of red circles with a black dot in the center.